Hubungan Kecemasan dengan Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 di RSUD Salatiga - Syari'ati, Atika Widya, dr. Nur Hidayat, Sp. PD, dr. Erika Diana Risanti (2015)
Background: Diabetes Mellitus (DM) is chronic condition that prevalent is increase in years. The people with DM may have two time high risk to anxiety compare with the other without DM. Anxiety disease relation with hyperglycemia of DM people. Hyperglycemia in long time causes destroy of the organ. Purpose: To analize correlation between anxiety and blood sugar levels of DM patient type 2. Method: This research uses analytic observational design research with cross sectional planning. The research conduct in Intern Disease Medical Clinic RSUD of Salatiga in December 2014. Sampling technique uses purposive sampling. Anxiety data got from questionnaire T-MAS, while data blood sugar levels of DM type 2 patients from medical scan. Data analyzes with Pearson test, if there is a normal data distribution. Because in this research the data is abnormal distribution, so it analyzes with non parametric spearman with SPSS 17.0 for windows. Result: Sample uses 40 respondents and 75% of respondents have anxiety. Sum 75.5% samples have bad diabetes mellitus. According to spearman correlation get p value = 0,000 and R = 0,902. It shows positive the power correlation between anxiety and blood sugar levels of diabetes mellitus patient type 2. Patients with higher anxiety then the blood sugar levels are also higher. Conclusion: There is correlation between anxiety and blood sugar levels of DM patient type 2 at RSUD of Salatiga.